Evaluation of Actin-1 Expression in Wild Caught Wuchereria bancrofti-Infected Mosquito Vectors. (1st October 2020) - Entonu, Moses Edache; Muhammad, Aliyu; Ndams, Iliya S.
Abstract : Background . Wuchereria bancrofti is the major cause of lymphatic filariasis transmitted by mosquito vectors. In the vector-parasite interaction and among other proteins, actin-1 has been implicated for successful transmission of the pathogen in laboratory-controlled experiments. However, validation of this finding from the pathogen's natural environment is required. Objective . This study is aimed at evaluating actin-1 expression upon Wuchereria bancrofti infection in mosquito vectors collected during an epidemiology study in Tsafe Local Government Area of Zamfara State, Nigeria. Methods . Mosquitoes were collected and identified using morphological keys, which include length of maxillary palps, pale spots on the wings, and scale patterns on the abdomen. This was followed by detection of the 188 bp SspI marker of Wuchereria bancrofti infection using polymerase chain reaction (PCR). The mRNA levels of the actin-1 gene were evaluated in the infected Anopheles gambiae sl and Culex quinquefasciatus and their controls, which were adult reared from the larvae in the study area. Results . The mosquitoes were identified to be Anopheles gambiae sl and Culex quinquefasciatus, while infection by Wuchereria bancrofti was confirmed by amplification of the 188 bp SspI marker. A 4.85 and 4.09 relative fold increase in actin-1 gene expression in Wuchereria bancrofti -infected Anopheles gambiae sl and Culex quinquefasciatus was observed. Thus, for the first time we reported that the actin-1 gene in wild caught mosquito vectors ( Anopheles gambiae sl and Culex quinquefasciatus ) infected with Wuchereria bancrofti is upregulated. Conclusion . The actin-1 gene is upregulated and similarly expressed during W. bancrofti infection in mosquito vectors in the study area and this may likely serve as a biomarker and viable strategy for the control of parasite transmission in endemic areas.